PELATIHAN HIDROPONIK DENGAN STYROFOAM BEKAS UNTUK MENINGKATKAN KETERAMPILAN SISWA MTS SENDANG TUBAN - Denny Nurdiansyah; Syarif Husen; Muhammad Shofiyudin; Muhammad Maftuchin (Yayasan Education and Social Center, 2022)
Hydroponics is an agricultural technique which can be done either in rural and urban. The problem this system is still a bit that will apply it especially in rural areas. To realize our agricultural system, needed the introduction of hydroponic simple to student elementary school in rural areas as an alternative to agriculture in the future. Do community service activities aims to introduce hydroponics and increase interest and ability of student elementary school in studying and practicing the agricultural system by means of hydroponics simple to use former styrofoam. The implementation of the community method devotion provided through the learning methods for theory and practice. The outcome of the activities devotion the community is to give the understanding of the theory and empirical hydroponics and to increase skills of students in Madrasah Tsanawiyah Al Hasaniyyah Kecamatan Senori in Kabupaten Tuban. Making simple hydroponic, enhancement of skill and eager to study of students can activate interaction among students and saving the environment from garbage